Alternative oxidase (AOX) in the carnivorous pitcher plants of the genus Nepenthes: what is it good for? - Pavlovič, Andrej; Kocáb, Ondřej (Annals of botany, 2022)
BACKGROUND AND AIMS: The carnivorous pitcher plants of the genus Nepenthes have evolved modified leaves that act as pitcher traps. The traps are specialized for prey attraction, capture, digestion and nutrient uptake but not for photosynthetic assimilation. METHODS: In this study, we used antibodies against different photosynthetic (D1, Lhcb2, Lhcb4, RbcL) and respiratory-related (AOX, COXII) proteins for semi-quantification of these proteins in the assimilation part of the leaves and the pitcher traps of different Nepenthes species and hybrids. Different functional zones of the trap and the traps from different ontogenetic stages were investigated. The pitcher traps of the distantly related species Sarracenia purpurea ssp. venosa were used as an outgroup. In addition, chlorophyll fluorescence and infrared gas analysis were used for measurements of the net rate of photosynthesis (AN) and respiration in the dark (RD). KEY RESULTS: The pitcher traps contained the same or lower abundance of photosynthesis-related proteins in accordance with their low AN in comparison to the assimilation part of the leaves. Surprisingly, all traps contained a high amount of alternative oxidase (AOX) and low amount of cytochrome c oxidase subunit II (COX II) than in the assimilation part of the leaves. Thermal imaging did not confirm the role of AOX in pitcher thermogenesis. CONCLUSIONS: The pitcher traps contain a high amount of AOX enzyme. The possible role of AOX in specialized pitcher tissue is discussed based on knowledge of the role and function of AOX in non-carnivorous plants. The roles of AOX in prey attraction, balance between light and dark reactions of photosynthesis, homeostasis of reactive oxygen species, digestive physiology and nutrient assimilation are discussed.
Keywords: cytochrome c oxidase; Carnivorous Plant; respiration; Sarracenia purpurea; Organic Chemicals; mitochondriální proteiny; Oxidoreductases; Sarraceniaceae; masožravé rostliny; Mitochondrial Proteins; Nepenthes; pitcher plant; organické látky; Plant Proteins; carnivorous plant; photosynthesis; oxidoreduktasy; Alternative oxidase; rostlinné proteiny